PROPOSTA DE INSTRUMENTO POR ATRIBUTOS INFORMADOS PELOS CONSUMIDORES AUTOMOTIVOS: UMA BUSCA POR FATORES DE VALORIZACAO DA MARCA PELA SATISFAÇAO COM O PRODUTO - Vieira, Leandro do Nascimento (2014)
The research problem targeted at this study relates to the environment of the automotive market, where the purchaser does not always feel satisfied about what the industry develops to sell him. Between the automobile user and the producer of this kind of item, there is a communication gap, even though there is a continuous development of strategies to produce material goods based on the personal opinion of those who buy them. For decades now, people have been talking about costumer service and massive progress has been made in the field of total quality linked to purchaser satisfaction. This dissertation aims to investigate which are the functional, aesthetic, welfare and financial items that define the automobile improvement; and in which order these items are organized to carry out the creation of structurally produced goods, beginning with the serial assembly, to satisfy the buyer. To do that, the researcher decided to, first, investigate and define which are the signals established for the product modeling, that is, the most relevant sub-themes, for, then, to carry out the structuring of an instrument of research. Surveys were conducted based on a questionnaire, which is both qualitative and quantitative, as well as based on the collected data, which, after being analyzed and synthetized, showed that the automobile functional and aesthetic characteristics are below the financial and welfare features. They also show that the brand (name of the automobile producer), definitely, does not act as a guide for the choices made by this kind of consumer. Based on the theoretical framework used here, we expect that the conclusive aspects presented here get useful to companies as well as for other studies in the areas of Engineering, Administration, Management and Design.